Predicting and Scoring Estuary Ecological Health Using a Bayesian Belief Network - Zeldis, John R.; Plew, David R. (Frontiers in Marine Science, 2022)
Excessive nutrient and sediment inputs threaten ecological condition in many estuaries. We describe a Bayesian Belief Network (BBN) that calculates an Estuary Trophic Index (ETI) score ranging between 0 (no symptoms of eutrophication) to 1 (grossly eutrophic) for estuaries in Aotearoa New Zealand (NZ). The ETI BBN includes estuary physiographic characteristics (estuary type, flushing time, intertidal area, estuary closure state, water column stratification) and nutrient and sediment loads available from existing geospatial tools and databases, that drive responses of ‘primary’ indicators (macroalgae and phytoplankton biomass) and ‘secondary’ indicators (or symptoms) of estuary ecological impairment (sediment carbon, sediment apparent redox potential discontinuity depth, water column oxygen, macrobenthos and seagrass condition). Relationships between the BBN nodes are based primarily on observational and model-based information from NZ and international studies rather than expert opinion. The model can be used in a purely predictive manner under knowledge-poor situations, using only the physiographic drivers and nutrient / sediment loads, or refined using field-derived observations of indicator values to reduce the uncertainty associated with the probabilistic BBN score. It is designed for shallow tidal lagoons, tidal river estuaries and coastal lakes; systems which are sensitive to eutrophication and sedimentation pressure and are common to NZ and globally. Modelled ETI BBN scores agreed well with ETI scores calculated from observed indicator values for 11 well-studied NZ estuaries. We predict ecological condition of 291 NZ estuaries, most of which have no monitored information on trophic state. We illustrate capabilities of the ETI BBN with two case studies: to evaluate improvements in estuary health arising from diversion of wastewater from an estuary via an ocean outfall, and to estimate catchment diffuse nutrient load reductions required to meet estuary health objectives. The ETI BBN may serve as a template for other agencies wishing to develop similar tools.